2024
DOI: 10.1021/acs.jafc.3c07154
|View full text |Cite
|
Sign up to set email alerts
|

Cow’s Milk Allergy May Induce Lipid Metabolism Disorder in BALB/c Mice via Exosomes

Xin Ma,
Jiaheng Xia,
Deming Gong
et al.

Abstract: Allergic diseases and lipid-metabolism-disorder-derived diseases are both significant public health issues. Recent studies have shown that exosomes are associated with the course of allergic diseases and are involved in lipid metabolism. In this study, exosomes derived from cow's milk allergic (CMA) mice medially loaded lesser proteins favoring cholesterol metabolism. The levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-c) in the serum were increased in the CMA mice, and hepatic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Lipid metabolism disorder represents an imbalance in lipid homeostasis, encompassing aberrations in lipid accumulation, lipogenesis, and disorders in fatty acid beta-oxidation. , Dysregulation of lipid homeostasis can precipitate obesity, chronic kidney disease (CKD), or other metabolism-related disorders. , In this study, the levels of each phospholipid class were increased in the HFD group. As shown in Figure A, compared with the ND group, the levels of LPC, LPE, PC, PE, and PG were significantly increased in the HFD group ( p < 0.001), and PS and PI were increased to some extent, although there was no significant difference, which indicated that HFD led to deregulated lipid metabolism in the mouse kidneys.…”
Section: Resultsmentioning
confidence: 72%
“…Lipid metabolism disorder represents an imbalance in lipid homeostasis, encompassing aberrations in lipid accumulation, lipogenesis, and disorders in fatty acid beta-oxidation. , Dysregulation of lipid homeostasis can precipitate obesity, chronic kidney disease (CKD), or other metabolism-related disorders. , In this study, the levels of each phospholipid class were increased in the HFD group. As shown in Figure A, compared with the ND group, the levels of LPC, LPE, PC, PE, and PG were significantly increased in the HFD group ( p < 0.001), and PS and PI were increased to some extent, although there was no significant difference, which indicated that HFD led to deregulated lipid metabolism in the mouse kidneys.…”
Section: Resultsmentioning
confidence: 72%